La correspondance de motifs, un outil pour l’analyse du discours ? - Marine Riguet; Mohamed Amine Boukhaled (Humanités Numériques)
In the second half of the 19th century, some French literary critics proclaimed the scientific nature of their discourse and regarded scientific essays (in biology, medicine, anthropology, psychology or sociology) as models. This article proposes to conduct a preliminary study to identify a possible discursive common ground between literary criticism and the sciences at the end of the 19th century. To do so, our study is based on a computational method, using extraction and correspondence analysis (CA) for syntactic patterns. Rather than a stylistic analysis, we undertake here a transdiscursive exploration, led by the discovery of relevant patterns in a text within a given corpus.